Biomechanical Parameters of the Cornea in Patients Who are Candidates for Laser Refractive Surgery with Complex Myopic Astigmatism and Dry Eye Syndrome - О. A. Klokova; S. N. Sakhnov; A. G. Zabolotniy; M. B. Аliev; A. I. Kacharov (Oftalʹmologiâ, 2024)
Purpose. To analyze the corneal indices obtained during examination with the Corvis® ST device of myopic patients — candidates for laser refractive surgery with dry eye syndrome (DES), before and after its treatment.Patients and methods. Study group I consisted of 88 patients with mild to moderate dry eye syndrome according to the classification of the International Seminar on Dry Eye Syndrome (TFOS DEWS II Definition and Classification Report), group II — 88 patients with no signs of corneal-conjunctival xerosis with complex myopic astigmatism at the age of 18 to 45 years (29.01 ± 7.68). The study of biomechanical parameters of the patients’ cornea was carried out using Corvis® ST (Oculus, Germany).Results. During the initial examination, six out of ten biomechanical indicators (DAM, A1T, A1V, A2T, A1L, SP_A1) in patients of study group I were significantly different (p < 0.05) from the indicators of study group II, the rest (A2V, A2L, HC_time, PD) were comparable (p > 0.05). Complex indices CBI, BAD_D in patients with DES were also statistically significantly (p < 0.05) different from those of patients without signs of DES and did not change after treatment for DES (p > 0.05). During the initial examination of patients in group I, 37 patients (42 %) had TBI in the range of 0.5–0.9. Against the background   of conservative treatment of dry eye syndrome, the number of such patients decreased to 20 (22 %), and with a TBI level of up to 0.3 it increased to 30 (34 %).Conclusion. The values of corneal biomechanical parameters determined during examination on Corvis® ST in patients with dry eye syndrome are different from those of patients without symptoms of corneal-conjunctival xerosis. Improving the condition of the ocular surface against the background of drug correction of dry eye syndrome and, as a result, improving the TBI index, provides a better selection of patients for laser refractive surgery and the choice of method for its implementation. The influence of asymptomatic dry eye syndrome in a significant number of patients on the value of corneal parameters studied on Corvis® ST determines the need for preventive diagnosis of dry eye disease in the general algorithm for examining all patients before refractive surgery.